Dinuclear gold catalysis - Wang, Wenliang; Ji, Cheng-Long; Liu, Kai; Zhao, Chuan-Gang; Li, Weipeng; Xie, Jin (Chemical Society reviews, 2021)
Gold chemistry has developed extensively in the past decade, and a dozen good reviews have been presented discussing this progress. Few however have paid close attention to the progress in organic synthesis of dinuclear gold-catalysis. A dinuclear gold catalyst is defined here as a gold complex with two gold centers linked by a bidentate ligand. With theoretical analysis and some representative studies in recent years, this comprehensive review highlights the particular properties of dinuclear gold-complexes, especially aurophilic interactions, and systematically summarizes the recent achievements of dinuclear gold-catalyzed coupling reactions, asymmetric catalysis, and photocatalysis, where dinuclear gold catalysts tend to show a greater advantage than the mononuclear gold catalysts. This review summarizes the recent achievements of dinuclear gold-catalyzed redox coupling, asymmetric catalysis and photocatalysis. The dinuclear gold catalysts show a better catalytic performance than the mononuclear gold catalysts in certain cases.